Same-Sex Sexuality and Educational Attainment: The Pathway to College. Issue 4 (21st March 2017) - Pearson, Jennifer; Wilkinson, Lindsey
ABSTRACT: Research finds lower levels of academic performance among sexual minority high school students, but some studies suggest sexual minorities have higher levels of educational attainment in adulthood. To further our understanding of how and why sexual orientation is associated with educational success, this study turns attention to the pathways to college completion, examining points along educational trajectories in which sexual minorities fall behind or surpass their heterosexual peers. Using data from the National Longitudinal Study of Adolescent to Adult Health, we find that sexual minority women are less likely than women with no same-sex sexuality to complete college, in part due to their high school performance and transition into college. Men who experience same-sex sexuality only in adolescence struggle in high school, but men who experience same-sex sexuality for the first time in adulthood are more likely to earn a college degree than men who do not experience same-sex sexuality.